Direct public oversight of government affairs - Mustafa Rasool Hussain (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Direct Control by the people on government decisions and actions, is an important issue because the people are the source of all authorities ,Direct control will be done through ( general opinion, political parties ,and media) while Indirect control will be done through ( parliamentary control ,the organization for controlling Administrative and financial activites ) the main question that arises is, what is the philosophical and legal basis of Direct Control? Therefore ,we divide our reseach In two Section in the first Section we explain the philosophical and legal basic of control.and in the second we explore the forms of control.